(untitled) (International Journal of Environmental Sciences, 2025)
Background: Respiratory diseases in sheep may result in sudden death or protracted illness, reducing feed efficiency, productive and reproductive performances in addition to causing slaughter condemnations. Mycoplasma ovipneumoniae is one of the main pathogens of sheep pneumonia, which becoming increasingly serious in sheep in Iraq.Aims: Isolation of M. ovipneumoniae from the suspected pneumonic sheep, and then, molecular confirmation of study isolates using the conventional molecular assay. Also, antibiotic susceptibility testing was conducted to indicate the sensitivity of M. ovipneumoniae isolates to different antibiotics.Materials and methods: A total of 37 pneumonic adult sheep were subjected to collection of nasal swabs that transported into PPLO broth, and cultured on PPLO agar. The isolates of M. ovipneumoniae were subjected to molecular examination by the conventional polymerase chain reaction (PCR). The Kirby-Bauer disc diffusion susceptibility test was served to determine the susceptibility patterns of M. ovipneumoniae isolate against 10 types of antibiotics using the Muller Hinton agar.Results: An overall 13.51% of study sheep were positive to M. ovipneumoniae that forms distinctive colonies on PPLO AGAR with generally small, appearing as tiny dew drops or resembling fried eggs. Light microscopy revealed blue Dienes staining of the colonies, indicating that they were Mycoplasmas. Oil microscopy showed lavender Giemsa staining of the cell body, with a predominance of spherical and filamentous forms. Targeting the 16S rRNA gene, molecular findings of the conventional PCR assayrevealed that all study isolates were M. ovipneumoniae (100%). Relation to antibiotic susceptibility,significant higher rate of resistance was seen in Amoxicillin and Penicillin G (100%) while lower rate of resistance was shown in Florfenicol, Norfloxacin, and Tylosin (0%). Subsequently, the higher rate of intermediate sensitivity was recorded in Ciprofloxacin, Florfenicol, and Gentamicin (40%); whereas, the lower rate of sensitivity was detected in Amoxicillin and Penicillin G (0%). However, significant higher rate of sensitivity was observed in Norfloxacin and Tylosin (100%); while, the lowest values wererecorded in Amoxicillin, Ciprofloxacin, and Penicillin G (0%). Conclusion: Mycoplasma ovipneumoniae is primarily found in clinically pneumonic sheep. However, additional research into survival of individuals that have been exposed to M. ovipneumoniae and subsequently recovered could help elucidate the potential long-term impacts of polybacterial pneumonia.